Prevalence and Associated Factors of Insomnia Syndrome in the Elderly Residing in Kahrizak Nursing Home, Tehran, Iran - F Mousavi; AA Tavabi; E Iran-Pour; R Tabatabaei; B Golestan (Tehran University of Medical Sciences, 2012)
Background: As insomnia is common, especially among the elderly in the nursing homes, we aimed to estimate insomnia prevalence among the elderly residing in nursing homes as well as to determine factors associated with insomnia in the elderly. Methods: This cross-sectional study was carried out in 2009 on 772 elderly residents at Kahrizak Nursing Home, Tehran Iran. The information was gathered through 5-part questionnaires by interviewing either the individuals or the nurses in charge and also reviewing the subjects' medical files. Eventually, the necessary data were analyzed using one-way ANOVA and Chi-square tests. Results: The mean age of the participants was 76.8 ± 8.05 years (range, 65 to 107 years). Based on the results, 303 (39.2%) of the elderly, including 86 (34.7%) men and 217 (41.1%) women, had insomnia syndrome. 433 (56.1%) participants complained of difficulty initiating sleep, 357 (46.2%) of disrupted sleep, 362 (46.9%) of early morning awakening, and 313 (40.5%) of non-restorative sleep. Our findings also showed that age (P = .004), number of diseases (P = .019), motility status (P = .017), sleep environment satisfaction (P < .001), cognitive status (P = .023), and functional autonomy (P = .003) were significantly associated with insomnia. Conclusion: Insomnia is a prevalent disorder amongst the nursing home elderly population, especially elderly women, and several pharmaceutical and nonpharmaceutical factors may trigger its occurrence. However, to prevent this problem, further studies are required in Iran and Middle Eastern region to establish a reliable understanding about insomnia patterns, causes, and cures.